Istanti, Frediana PENGARUH HARGA, KEPERCAYAAN, KEMUDAHAN BERBELANJA DAN E-PROMOSI TERHADAP KEPUTUSAN PEMBELIAN BELANJA ONLINE DI KOTA SURABAYA (JBT (JURNAL BISNIS dan TEKNOLOGI), 2017)
The purpose of this study is to determine how the effects of price, trust, ease of shopping and E-promotion on purchasing decisions online shopping. This type of research is explanatory research with data collection using questionnaire. This study uses the 100 respondents who made a purchasing decisions online shopping. The sampling technique of this study was purposive sampling. The analysis instrument is validity test and reliability test. Data analysis that used is correlation coefficient, coefficient of determination, simple linear regression, t test, multiple linear regression,andFtest. The results of this research indicate that: (1) there is a positive effect of price on the buying decisions of online shopping by the t value of 3,618; significance value of 0.000<0,05 and regression coefficient of 0,274, (2) there is a positive effect of trust on the buying decisions of online shopping by the t value of 2,917; significance value of 0.004<0,05 and regression coefficient of 0,218, (3) there is a positive effect of ease of shopping on the buying decisions of online shopping by the t value of 3,669; significance value of 0.000<0,05 and regression coefficient of 0,2740,(4) there is a positive effect of epromotion on the buying decisions of online shopping by the t value of 3,223; significance value of 0.002<0,05and regression coefficientof 0,238,and (5)there is apositive effect of price, trust, ease of shopping, e promotion on buying decisions online shopping, evidenced by the calculated F value of 21,397 with a significance of 0.000<0.05